Magical realism and representations of the cold war in Southeast Asia - Lye, Kit Ying (2016)
The geo-political landscape of Southeast Asia is fertile ground for a literature that engages with the marvellous, just as the South American and Caribbean landscape did for Latin American authors. However, while there are acknowledgements by scholars that religious myths and pre-existing animistic beliefs continue to influence the way that the indigenous people understand their worlds, Southeast Asian authors (unlike many of their postcolonial peers), do not actively employ magical realism in their exploration of history and civil unrest in their writings, and when they do, are not employed to the same degree as postcolonial authors in other regions. Moreover, the lack of scholarship on postcolonial issues in Southeast Asia literature further obscures any understanding of how its literature engages with and employs magical realism. This “lack ” is perhaps best understood by seeking to understand the terror and silence that “binds” Southeast Asia together during the Cold War, and which has affected the literature produced in that time. By reading a selection of novels and short stories from the Philippines, Indonesia, Timor Leste, and Cambodia that discuss several newly independent nations’ struggles during the Cold War period, we can re-examine a literature that has not been studied as extensively as other similar political literature. To this end, we may begin to understand why there is very little engagement with magical realism in the region’s contemporary literature, and in the process identify how Southeast Asian literature developed differently than other postcolonial modes.